1990
DOI: 10.1002/hon.2900080106
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of mitozantrone in combination with chlorambucil and prednisolone for relapsed and refractory non‐Hodgkins lymphoma

Abstract: Thirty-six patients with non-Hodgkin's lymphoma (NHL) (comprising patients with refractory or relapsed disease and eight elderly, unfit patients with de novo disease) were treated with mitozantrone, chlorambucil and prednisolone on an out-patient basis. Fifteen patients had low grade (LG) disease, five patients intermediate grade (IG) disease and 16 patients high grade (HG) disease and 31/36 had stage IV disease. All elderly patients had IG or HG disease. The regimen was well-tolerated. After six courses of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…This confirms the findings of previous studies [4,20] which suggested a role for anthracyclines in the treatment of LGNHL. The triple combination was well tolerated and, whilst the addition of the anthracycline added to overall toxicity, Grade IV toxicity was rare and there were no treatment related deaths.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This confirms the findings of previous studies [4,20] which suggested a role for anthracyclines in the treatment of LGNHL. The triple combination was well tolerated and, whilst the addition of the anthracycline added to overall toxicity, Grade IV toxicity was rare and there were no treatment related deaths.…”
Section: Discussionsupporting
confidence: 93%
“…The addition of vincristine and prednisolone resulted in a higher remission rate [3] but results for overall survival were disappointing. In 1990 preliminary results from a pilot study suggested some benefit from the addition of the anthracenedione, mitozantrone, to the combination of chlorambucil and prednisolone [4] and led to our phase II study of the efficacy of the addition of an oral anthracycline (idarubicin) to the combination of chlorambucil and dexamethasone (CID) [5]. Results from that study showed that the treatment was well tolerated and effective with a 5 year event free survival (EFS) of 22% and overall survival (OS) of 65%.…”
Section: Introductionmentioning
confidence: 97%